Habituation of the responsiveness of mesolimbic and mesocortical dopamine transmission to taste stimuli - De Luca, Maria Antonietta (Frontiers in Integrative Neuroscience, 2014)
The presentation of novel, remarkable, and unpredictable tastes increases dopamine (DA) transmission in different DA terminal areas such as the nucleus accumbens (NAc) shell and core and the medial prefrontal cortex (mPFC), as estimated by in vivo microdialysis studies in rats. This effect undergoes adaptive regulation, as there is a decrease in DA responsiveness after a single pre-exposure to the same taste. This phenomenon termed habituation has been described as peculiar to NAc shell but not to NAc core and mPFC DA transmission. On this basis, it has been proposed that mPFC DA codes for generic motivational stimulus value and, together with the NAc core DA, is more consistent with a role in the expression of motivation. Conversely, NAc shell DA is specifically activated by unfamiliar or novel taste stimuli and rewards, and might serve to associate the sensory properties of the rewarding stimulus with its biological effect (Bassareo etal., 2002; Di Chiara etal., 2004). Notably, habituation of the DA response to intraoral sweet or bitter tastes is not associated with a reduction in hedonic or aversive taste reactions, thus indicating that habituation is unrelated to satiety-induced hedonic devaluation and that it is not influenced by DA alteration or depletion. This mini-review describes specific circumstances of disruption of the habituation of NAc shell DA responsiveness (De Luca etal., 2011; Bimpisidis etal., 2013). In particular, we observed an abolishment of NAc shell DA habituation to chocolate (sweet taste) by morphine sensitization and mPFC 6-hydroxy-dopamine hydrochloride (6-OHDA) lesion. Moreover, morphine sensitization was associated with the appearance of the habituation in the mPFC, and with an increased and delayed response of NAc core DA to taste in naive rats, but not in pre-exposed animals. The results here described shed light on the mechanism of the habituation phenomenon of mesolimbic and mesocortical DA transmission, and its putative role as a marker of cortical dysfunction in specific conditions such as addiction.